MICROCONTROLLER-BASED pH AND TURBIDITY MEASURING SYSTEM - Myint, Cho Cho; Soe, Maung Maung (MATTER: International Journal of Science and Technology, 2018)
Sustaining and monitoring appropriate pH levels is important in agricultural, industrial and environmental processes. For measurement of the pH level, it is essential to choose the correct pH probe. Turbidity can be measured by turbidity meters for the assessment of water quality or the proficiency of purification process.Research Objectives: To investigate the water quality of streams and lakes, to measure various pH levels of liquids and to measure different turbidity values of liquids.Methodology: The microcontroller based pH level and turbidity measuring system is designed and constructed using a pH probe -KADY pH tester / meter, amplifier circuit, turbidity sensor, PIC 16F887 microcontroller circuit, 16 x 2 line LCD module and power supply circuit.Findings and Research outcomes: In pure water, pH is 5.5-6.9 and voltage is 700-720mV. In coca, pH is 2-3 and voltage is 620 – 640 mV. In salt water, pH is 9-10 and voltage is 780-800 mV.In orange, turbidity is 300-900 NTU and voltage is 1.0V-0.7V. In coca, turbidity is 65-80 NTU and voltage is 1.4V – 1.58V. In milk, turbidity is >4000 NTU and voltage is 0-0.1 V. Conclusion: The pH sensor circuit and turbidity sensor circuit can be assembled together with constructed microcontroller circuit